A határon átnyúló agglomerációk turizmusának típusai - Székely, Andrea (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The new borders of Hungary in 1920 cut cities and agglomerations inducing their fallback, but the new situation favoured the creation of new functional centers. The closed boundaries after World War II resulted the development of spatial structures inside the national borders. At the same time, in Western Europe border urban areas organic development started, and they shaped cross-border agglomerations. The soundest example is the French-Belgian Lille cross-border metropolis. After the political changes, the cross-border cooperation based on real common socio-economic interest has become possible in Hungary. This processus is encouraged by the EU through its regional (Interreg, Espon) and urban (Urban, Urbact) programs. The analysis of cross-border agglomerations may be one of the axes of the Hungarian regional researches in the near future.